Development of Food Chemistry, Natural Products, and Nutrition Research - Santini, Antonello; Cicero, Nicola (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue is dedicated to gathering the latest advances in the food sources, chemistry, analysis, composition, formulation, use, experience in clinical use, mechanisms of action, available data of nutraceuticals, and natural sources that represent a new frontier for therapy and provide valuable tools to reduce the costs for both environment and healthcare systems.